(untitled) (International Journal of Engineering and Computer Science, 2017)
Due to non-stop increase of communication subscribers, the loss and distortion of data (voice, video…) is emphasized. Meanwhile, IEEE-SA (Standard Association) has developed a new standard for advanced audio coding (AAC) in August 2013, called IEEE 1857.2 for contributing to those issues. This new standard for AAC is an efficient lossless audio codec (coding decoding) technique, in improving audio quality for compression and decompression, optimizing bandwidth during transmission, saving storage space, speeding up the video streaming, audio streaming and others video or audio data. This survey consists not only of describing the different existing techniques for lossless audio compression, and also of showing the state of the art of this recent lossless standard for AAC upon its most popular predecessors.